2017
DOI: 10.1002/2017jc012805
|View full text |Cite
|
Sign up to set email alerts
|

Relative influences of the metocean forcings on the drifting ice pack and estimation of internal ice stress gradients in the Labrador Sea

Abstract: Understanding the relative influences of the metocean forcings on the drift of sea ice floes is a crucial component to the overall characterization of an ice environment and to developing an understanding of the factors controlling the ice dynamics. In addition, estimating the magnitude of the internal stress gradients on drifting sea ice floes generated by surrounding ice cover is important for modeling operations, informing the design of offshore structures and vessels in ice environments, and for the proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 17 publications
0
13
1
Order By: Relevance
“…The sensitivity analysis revealed that out of the four drag coefficients, the sea-ice force magnitudes on the ice island fragments were most sensitive to the water form drag coefficient, followed by the air form drag coefficient. The force records from the residual approach (Turnbull and others, 2017) also revealed that the sea-ice force magnitudes were almost insensitive to varying the skin drag coefficients for both air and water (Figs 13a, c). These results are expected given that the values of skin drag coefficients are significantly lower than form drag coefficients and that higher proportions of the fragments' walls were exposed to water than to air.…”
Section: Discussionmentioning
confidence: 72%
See 4 more Smart Citations
“…The sensitivity analysis revealed that out of the four drag coefficients, the sea-ice force magnitudes on the ice island fragments were most sensitive to the water form drag coefficient, followed by the air form drag coefficient. The force records from the residual approach (Turnbull and others, 2017) also revealed that the sea-ice force magnitudes were almost insensitive to varying the skin drag coefficients for both air and water (Figs 13a, c). These results are expected given that the values of skin drag coefficients are significantly lower than form drag coefficients and that higher proportions of the fragments' walls were exposed to water than to air.…”
Section: Discussionmentioning
confidence: 72%
“…9.The concentration of sea ice surrounding the four ice island fragments during the analyzed drift periods, obtained from CIS daily ice charts.
Fig. 10.Sea-ice force magnitudes on the ice island fragments tracked by beacons 6640, 1700 and 5640, calculated using a residual approach (Turnbull and others, 2017) and Lichey and Hellmer's model (2001). The second y -axis (on the right) indicates the sea-ice concentration out of 10 (green lines) in the vicinity of the ice island fragments.
…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations